2021
DOI: 10.3390/medicina57111156
|View full text |Cite
|
Sign up to set email alerts
|

Histology and Immunohistochemistry of Radial Arteries Are Suggestive of an Interaction between Calcification and Early Atherosclerotic Lesions in Chronic Kidney Disease

Abstract: Background and Objectives: recent studies suggest an implication of immune mechanisms in atherosclerotic disease. In this paper, the interaction between inflammation, calcification, and atherosclerosis on the vessel walls of patients with chronic kidney disease (CKD) is described and evaluated. Materials and Methods: patients with stage V CKD, either on pre-dialysis (group A) or on hemodialysis (HD) for at least 2 years (group B), in whom a radiocephalic arteriovenous fistula (RCAVF) was created, were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…In contrast, RANKL and RANK are mostly undetectable on the normal vascular wall, but their expression is significantly increased in calcified areas [ 16 ]. Immunohistochemistry performed on calcified areas of the arterial wall of CKD patients revealed that the calcification process is strongly regulated by immunological factors and that the degree of vascular calcification was positively correlated with the intensity of OPG expression, whereas intima media thickness was associated with the degree of RANKL expression [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, RANKL and RANK are mostly undetectable on the normal vascular wall, but their expression is significantly increased in calcified areas [ 16 ]. Immunohistochemistry performed on calcified areas of the arterial wall of CKD patients revealed that the calcification process is strongly regulated by immunological factors and that the degree of vascular calcification was positively correlated with the intensity of OPG expression, whereas intima media thickness was associated with the degree of RANKL expression [ 33 ].…”
Section: Discussionmentioning
confidence: 99%